(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The prevailing daily wage rate for manual labour in 2004-05, it was necessary for at least three members of an agricultural labour household to get employment for more than 200 days in a year in order to maintain itself above the poverty level. We also noted that since in reality it is difficult for many households to get this much employment, the poverty level in rural households is still high. the ground reality continues to reveal disturbing trends. while the availability of foodgrains has come down in general (rural + urban) from about 510 grams in 1990-91 to about 444 grams in 2009, the per capita consumption of foodgrains in rural households has declined relatively more from 373 grams in 1987-88 to 313 grams in 2009-10. Further, besides a continued increase in the proportion of marginal farmers over time, among all the three classes of agricultural households (landless, marginal and small farmers), there is a significant income deficit (to a tune of 20 to 40 percent) to meet their minimum consumption needs. As a result, the rural households are indebted with the landless/marginal/small farmers segment being more dependent on informal lending sources to meet their minimum consumption needs. More specifically, while in the aggregate close to 50 percent of rural households are indebted, more than 60 percent of landless labour incur debt for meeting their consumption expenditure. The wages paid to rural labour are often far below the statutory minimum wage and are differentiated by gender, location and nature of work/activity. Due to these disturbing trends, the government in its mid-term appraisal of the Tenth Plan (2002-07) raised serious concern on the ‘distress’ experienced by agricultural labourers and marginal/small farmers. The government has since taken many steps to mitigate their hardship experienced. One of the notable initiatives of the government in the direction of providing guaranteed wage employment opportunities for rural unskilled manual labour was to enact a legislation The National Rural Employment Guarantee Act, (NREGA) in August 23, 2005. The Act guarantees employment at statutory minimum wages for all those persons who sought manual unskilled labour for at least up to 100 days in a year.